2020
DOI: 10.1007/s40962-020-00450-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Starting Microstructure in the Formation of Austenite at the Intercritical Range in Ductile Iron Alloyed with Nickel and Copper

Abstract: Intercritical austenitizing is a key step on the production of dual-phase austempered ductile iron. Therefore, understanding the formation of austenite at the intercritical range should provide critical information for the future development of this family of alloys. In this work, a ductile iron alloyed with copper and nickel (3.4 C, 2.6 Si, 0.9 Ni, 0.6 Cu, wt%) was studied. The as-cast alloy was submitted to ferritic annealing and normalizing in order to obtain fully ferritic and fully pearlitic microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Intercritical heat treatments can also be performed on DI to increase the mechanical properties. Intercritical heat treatments can be applied to obtain microstructures of graphite nodules in a matrix of ferrite and austenite particles or graphite nodules in a matrix of ferrite and tempered martensite (Aristizabal et al, 2012;Machado et al, 2020). Corrosion behavior, like mechanical properties, is related to the alloy microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Intercritical heat treatments can also be performed on DI to increase the mechanical properties. Intercritical heat treatments can be applied to obtain microstructures of graphite nodules in a matrix of ferrite and austenite particles or graphite nodules in a matrix of ferrite and tempered martensite (Aristizabal et al, 2012;Machado et al, 2020). Corrosion behavior, like mechanical properties, is related to the alloy microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In previous studies, DMS-ADI was named as dual-phase austempered ductile iron (DP-ADI) [9][10][11][12][13][14][15][16] , austempered ductile iron with dualmatrix structure (ADI with DMS) 1-3, 7, 8, 17, 18 , ductile cast iron with dual-matrix structure (DMS) 19,20 , dual-phase matrix austempered ductile iron (DPM-ADI) 21 , dual-matrix ductile iron (DM-DI) 22 , and intercritically austempered ductile iron (IADI). [23][24][25][26][27][28][29][30][31][32] The term dual-matrix structure was used first by Voigt et al in their study. 33 However, Wade&Ueada 34 first produced the dual-matrix structure in ductile irons and they had named it ductile cast iron with duplex matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]9,10,[35][36][37] Ausferrite has been defined as a mixture of bainitic ferrite (a b ) and high-carbon stabilized austenite (c HC ) in austempered ductile irons. 1,9,26,[38][39][40] The ausferritic structure provides a good combination of tensile strength, ductility, and impact toughness in the ADIs. 9,24,26,[41][42][43][44][45][46][47][48][49] Moreover, the ausferritic structures significantly improve the tribological properties of the ADIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that austenite formation is related to starting microstructure and austenite formation is faster with a starting microstructure of pearlite and it increases with the decreasing interlaminar spacing. 11 One of the most promising usage areas of ADI is in high load contact cases, with a number of studies having reported the wear and friction properties of DI under different conditions. Wen et al investigated the wear behavior of ADI using a ball on disk wear test setup.…”
Section: Introductionmentioning
confidence: 99%